STUDI EKSPERIMEN PENGARUH JUMLAH PIPA SALURAN TERHADAP PERFORMA TURBIN FRANCIS - Afif Nur Ayu Shadrina; Joke Pratilastiarso; Achmad Bahrul Ulum (PROSIDING SNAST, 2018)
The large population growth requires Indonesia to continue to build new power plants by utilizing the diversity of energy resources in Indonesia. PLTA is an integrated power system in a dam by utilizing the mechanical energy of the water flow to rotate the turbine. The francis turbine is one of the important components of hydropower that serves to convert or convert the potential energy form that water possesses into mechanical energy. Water flowing from the pipeline from a certain height can convert to pressure energy before entering the guide vane and some of the pressure energy is converted into kinetic energy as it passes through the guide vane. Some of that energy will drive the shaft or runner. The pipeline that serves to direct the flow before entering the spiral case can be varied by the number of single pipes up to three pipelines. The francis turbine is designed in a laboratory scale with a runner dimension of 30 cm and the number of 10 blades has a pipe dimension of 8.9 cm. The test results show that the trendline when using 2 pipelines is better than the other pipeline variation with the highest efficiency value of 6.2%.francis turbine